A model identification approach to quantify impact of whole-body vertical vibrations on limb compliant dynamics and walking stability. (June 2020) - Mahmood, Imran; Martinez-Hernandez, Uriel; Dehghani-Sanij, Abbas A.
Highlights: This study introduces methods to quantify vertical limb dynamics while walking. A model identification approach is proposed to quantify lower limb compliant dynamics. Linear control theory is applied to analyse the effect of vertical loading impacts on stability. Proposed methods are applied to investigate the structural impacts of wearable devices. Our methods show that a wearable orthosis has significant effect on the limbs' vertical dynamics. Abstract: Extensive research is ongoing in the field of orthoses/exoskeleton design for efficient lower limbs assistance. However, despite wearable devices reported to improve lower limb mobility, their structural impacts on whole-body vertical dynamics have not been investigated. This study introduced a model identification approach and frequency domain analysis to quantify the impacts of orthosis-generated vibrations on limb stability and contractile dynamics. Experiments were recorded in the motion capture lab using 11 unimpaired subjects by wearing an adjustable ankle–foot orthosis (AFO). The lower limb musculoskeletal structure was identified as spring-mass (SM) and spring-mass-damper (SMD) based compliant models using the whole-body centre-of-mass acceleration data. Furthermore, Nyquist and Bode methods were implemented to quantify stabilities resulting from vertical impacts. Our results illustrated a significant decrease ( p < 0.05) in lower limb contractile properties by wearing AFO compared with a normal walk. Also, stability margins quantified by wearing AFO illustrated a significant variance in terms of gain-margins ( p < 0.05) for both loading and unloading phases whereas phase-margins decreased ( p < 0.05) only for the respective unloading phases. The methods introduced here provide evidence that wearable orthoses significantly affect lower limb vertical dynamics and should be considered when evaluating orthosis/prosthesis/exoskeleton effectiveness.